An Integrated biomarker approach for explaining the potency of exogenous glucose on transportation induced stress in Labeo rohita fingerlings - Biswal, Abhilipsa (Sci Rep, 2021)
Transportation of fish seed is a complex phenomenon associated with multiple kinds of stressors that simultaneously affect the fish in a confined environment, causing stress and mortality. The present study investigated the stress-relieving effect of exogenous glucose as a water additive in different concentrations (0.1, 0.2, 0.3, and 0.4%) during simulated transportation (12 h) of L. rohita fingerlings. The integrated biomarker response (IBR) index is a holistic tool to determine the optimum dose of exogenous glucose for mitigating transportation stress in fish. Based on selected biomarkers related to the stress hormone, serum biochemistry, oxidative stress, and HSP70 mRNA expression, the IBR index is calculated for each treatment and control group. The result showed a significant change in the level of stress hormone cortisol, enzymes (SGPT, LDH, MDH, SOD, CAT) and metabolites (serum glucose, triglyceride, creatinine) along with an upregulation in liver HSP70 mRNA expression. IBR index suggests that 0.2% glucose exhibited the lowest multi-biomarker stress response in comparison to other treatments and control. Therefore, the use of 0.2% glucose as a water additive will provide a solution to transportation induced stress in L. rohita fingerling and will underwrite the success of grow-out fish culture in days to come.